2017
DOI: 10.1200/jco.2017.35.4_suppl.225
|View full text |Cite
|
Sign up to set email alerts
|

Gemox versus surveillance following surgery of localized biliary tract cancer: Results of the PRODIGE 12-ACCORD 18 (UNICANCER GI) phase III trial.

Abstract: 225 Background: No standard post-surgery adjuvant treatment is currently recommended in localized biliary tract cancer (BTC). Gemcitabine combined with platinum is the standard chemotherapy for advanced BTC. The aim of this phase III randomized trial was to assess whether GEMOX would increase relapse-free survival (RFS) while maintaining health-related quality of life (HrQoL). Methods: We performed a multicenter randomized phase III trial. Patients were randomized, within 3 months of R0 or R1 resection of a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 0 publications
2
47
0
5
Order By: Relevance
“…Results of a phase III trial conducted in France, however, demonstrated that adjuvant chemotherapy with gemcitabine and oxaliplatin (GEMOX), initiated 3 months after R0 or R1 resection of biliary tract cancer, did not significantly improve recurrence-free survival compared with placebo (HR 0.83, 95% CI 0.58–1.19; P = 0.31) 74 . More evidence is needed to clarify the role of adjuvant chemotherapy in the treatment of cholangiocarcinoma.…”
Section: Standard Of Care: Diagnosis and Therapymentioning
confidence: 99%
“…Results of a phase III trial conducted in France, however, demonstrated that adjuvant chemotherapy with gemcitabine and oxaliplatin (GEMOX), initiated 3 months after R0 or R1 resection of biliary tract cancer, did not significantly improve recurrence-free survival compared with placebo (HR 0.83, 95% CI 0.58–1.19; P = 0.31) 74 . More evidence is needed to clarify the role of adjuvant chemotherapy in the treatment of cholangiocarcinoma.…”
Section: Standard Of Care: Diagnosis and Therapymentioning
confidence: 99%
“…Two randomized phase III clinical trials exploring adjuvant chemotherapy were reported in 2017. Firstly, the results from the PRODIGE-12/ACCORD-18 clinical trial assessing the benefit of adjuvant combination chemotherapy compared with observation alone were reported in January 2017 (22). This multicenter phase III trial randomized 196 patients within 3 months of resection of a localized BTC (intra-hepatic, perihilar, extra-hepatic cholangiocarcinoma or gallbladder cancer), to receive either adjuvant gemcitabine and oxaliplatin or surveillance; there was no significant difference in relapse-free survival between the arms (hazard ratio of 0.83 (95%-CI 0.58–1.19); p-value 0.31).…”
Section: Clinical Contextmentioning
confidence: 99%
“…Furthermore, the generalizability of results from the only previous phase 3 trial evaluating adjuvant therapy for BTCs is unclear because of the high rate of margin‐positive resection (R+) and because the chemotherapy regimen and schedule evaluated in this study are uncommonly used in contemporary practice . Additional prospective, randomized trials of adjuvant therapy for localized BTCs are either ongoing or have recently finished accrual …”
Section: Introductionmentioning
confidence: 99%
“…Given existing uncertainty regarding the optimal management of BTC and the dearth of data about the benefits of both resection and adjuvant therapy for lymph node–positive disease, we used a national cancer registry to ascertain treatment patterns for patients with lymph node–positive BTC. Although we recognize the disparate nature of IHC, GBC, and extrahepatic cholangiocarcinoma (EHC), we believed it was important to attempt to study each, because they are included in all major randomized trials of adjuvant therapy for BTC and because the results generated herein could provide novel and potentially useful information for the treatment of these rare malignancies. The main objectives of this study were to understand the value of surgical resection in patients with lymph node–positive BTC and to evaluate any survival benefit associated with the receipt of adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%